Bone regeneration promoting drug-loaded skull implant with bionic structure and preparation method thereof

By adopting bionic structure and porous design in skull implants, combined with self-assembly technology of polydopamine-carboxymethylchitosan and hydroxyapatite, the biocompatibility and bone-promoting regeneration ability of skull implants are solved. The problem of insufficient results has achieved the stability of the implant and the sustained release effect of the drug.

CN119185657AInactive Publication Date: 2024-12-27SHANDONG BRANDEN MEDICAL DEVICE

Patent Information

Application Number
CN202411708201.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing skull implants have poor biocompatibility, loose displacement and inflammatory response in structure, and the material's mechanical properties and bone-promoting regeneration ability are insufficient.

Method used

The skull implant with a bionic structure was prepared by melt casting method, and the skull implant was molded by molding the cylindrical and spherical water-soluble core and PEEK mixture, combining the polydopamine-carboxymethyl chitosan coating and the self-assembly of hydroxyapatite. Porous implants with Haversi-like tubes and bone-like trabecular structures are formed and drug is covered on the surface of the implant to promote bone tissue regeneration.

Benefits of technology

The vascularized channels and bone tissue climbing of the implant are achieved, which improves biocompatibility and drug sustained release effect, enhances bone tissue regeneration ability, and reduces the risk of cytotoxicity and loose shift of the implant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119185657A_ABST
    Figure CN119185657A_ABST
Patent Text Reader

Abstract

The invention discloses a bone regeneration promoting drug-loaded skull implant with a bionic structure and a preparation method of the bone regeneration promoting drug-loaded skull implant, and belongs to the technical field of medical materials. The skull implant is prepared through a flat plate mold pressing technology and is of a bionic three-layer structure, the upper layer and the lower layer of the haft tube imitating structures and the middle layer of the bone trabecula imitating structure are prepared through the water-soluble core, a vascularization channel can be provided, and bone tissue climbing is promoted; a polydopamine-carboxymethyl chitosan coating is used for carrying out surface modification on a porous structure of the implant, hydroxyapatite in-situ forming and bone regeneration promoting medicine loading are achieved through an impregnation process, and the polydopamine coating can provide a hydration environment; hydroxyapatite in-situ forming increases biocompatibility on the premise of not influencing the mechanical properties of implants, in addition, hydroxyapatite degradation and drug release can jointly induce bone tissue regeneration, and skull repair is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a bone regeneration promoting drug-loaded skull implant with a bionic structure and a preparation method thereof, belonging to the technical field of medical materials. Background Art

[0002] Skull implants are mainly used to fill defective areas, restore the airtightness of the cranial cavity, and solve skull defect problems. They can protect brain tissue, promote cerebral blood flow and cerebrospinal fluid dynamic balance, and improve appearance, which helps to improve the patient's quality of life. Currently, skull implants can be divided into two types in terms of structure: traditional skull implants and porous bionic skull implants.

[0003] Traditional skull implants are mostly made of biologically inert materials or metal materials, with solid structures and poor biocompatibility. The implant surface is smooth and difficult to fuse with the surrounding bone tissue after implantation. Over time, it will gradually loosen or shift, affecting the stability of the implant and its compatibility with the surrounding bones. At the same time, the stimulation of the implant to the surrounding tissue may cause inflammatory reactions, infection, effusion and other problems.

[0004] Porous bionic skull implants are mostly made of polymer materials. A porous structure is formed by adding porogens or special molding methods, and then the porosity and pore size are controlled to achieve different pore structure designs, promote the fusion of bone tissue and implants, and achieve bone conduction. In addition, a variety of skull implants have been gradually developed by bionic bone structures that simulate the cortical bone and cancellous bone structure of the human body. The combination of porous structure and bionic structure can reduce the occurrence of implant loosening and displacement, making bone tissue fusion possible. However, the design of porous and bionic structures, the improvement of bone regeneration ability, and the realization of good interface integration are issues worthy of attention in the research of porous bionic skull materials.

[0005] Chinese patent CN 115715716 A discloses a skull implant with a porous bionic structure made of modified polyetheretherketone as raw material and prepared by 3D printing technology. 3D printing technology allows the implant to perfectly match the patient's skull defect, and the porous bionic structure provides space for postoperative bone growth and accelerates bone exchange, but its polyetheretherketone modified material is a mixture of polyetheretherketone and biphasic calcium phosphate ceramics. The degradation of calcium phosphate will effectively promote the proliferation and differentiation of bone cells while also deteriorating the mechanical properties of the implant, making it difficult to provide effective support in the later stage.

[0006] Chinese patent CN 116442476 A prepared a polyetheretherketone skull defect prosthesis containing a porous sand structure based on CNC machining methods, 3D printing and injection molding technology, and then formed a specific cavity in the middle layer through sand cleaning technology. The porous structure in the middle area can achieve the growth of scalp soft tissue, accelerate blood supply and cell migration and attachment process. Polyetheretherketone material can provide sufficient mechanical properties, but it is biologically inert, easily causes adverse inflammatory reactions, and the prosthesis preparation process is relatively complicated. Summary of the invention

[0007] One of the purposes of the present invention is to provide a bone regeneration promoting drug-loaded skull implant with a bionic structure in order to solve the above technical problems.

[0008] The second object of the present invention is to provide a method for preparing the above-mentioned bone regeneration-promoting drug-loaded skull implant with a bionic structure, which is carried out according to the following operating steps: (1) A cylindrical and spherical water-soluble core was prepared as a porogen by melt casting, and then mixed with polyetheretherketone (PEEK) and molded, and a skull implant with a bionic structure was initially obtained by a dissolution process; The upper and lower layers of the skull implant are a mixture of a cylindrical water-soluble core and PEEK, and the middle layer is a mixture of a spherical water-soluble core and PEEK; To better realize the present invention, further, the average diameter of the cylindrical water-soluble core is 0.2 ~ 1.4 mm, the length is 3 ~ 5 mm, the number is 10 ~ 20, and the cylindrical water-soluble cores in the upper and lower layers of the implant are mutually connected by a positioning mold design to form a Haversian tube structure; the spherical water-soluble core is used to simulate the trabecular bone structure of the middle layer and two ball diameter sizes are designed, which are 300 ~ 450 μm and 500 ~ 800 μm, respectively, and the porosity is 60% ~ 80%, and the porosity can be adjusted by the content of the spherical water-soluble core; when the water-soluble core is prepared by the melt casting method, the temperature of the resistance furnace is 600 ~ 900 ° C, and the insulation time is 5 ~ 60 min after the furnace temperature reaches the set temperature; To better implement the present invention, further, the mass ratio of the spherical water-soluble core to the PEEK mixture is 1:50 to 50:1; To better implement the present invention, further, the molding parameters are: cold pressing 1 ~ 20 MPa, hot pressing 1 ~ 15MPa, holding pressure 2 ~ 10 min; hot melt temperature 300 ~ 400 ° C, heating time 1.5 ~ 5.5 h; using an ultrasonic water bath to completely precipitate the porogen.

[0009] (2) adding carboxymethyl chitosan to a Tris buffer solution containing polydopamine, mixing and stirring to obtain a polydopamine-carboxymethyl chitosan mixed solution, immersing the skull implant prepared in step (1) therein, taking out and drying, to obtain a skull implant containing a polydopamine-carboxymethyl chitosan coating; To better implement the present invention, further, the concentration of the polydopamine solution is 0.2 to 1% m / v; polydopamine and carboxymethyl chitosan undergo Michael addition reaction in an alkaline environment and are grafted onto the surface of polydopamine, the concentration of carboxymethyl chitosan is 0.2% to 2% m / v, and the grafting time is ≥30 h; the skull implant is immersed in the polydopamine-carboxymethyl chitosan coating for 1 to 20 min, the drying temperature is 60°C, and the drying time is 5 to 10 min.

[0010] (3) preparing a hydroxyapatite coating by a bionic method, immersing the skull implant prepared in step (2) in a 1.5 times SBF solution in a constant temperature water bath to generate hydroxyapatite in situ, taking out and drying to obtain a skull implant containing polydopamine-carboxymethyl chitosan and a hydroxyapatite coating; To better realize the present invention, further, the active group phenolic hydroxyl group on the surface of the polydopamine-carboxymethyl chitosan coating can chelate calcium ions and induce the calcium and phosphorus ions provided by SBF to form hydroxyapatite nuclei according to the self-assembly mechanism, thereby spontaneously forming orderly and uniform hydroxyapatite on the surface of the polydopamine-carboxymethyl chitosan coating in situ; To better implement the present invention, further, the water bath temperature is 37°C, the soaking time is 3-12 days; the drying temperature is 60°C, and the drying time is 5 to 10 min.

[0011] (4) immersing the implant prepared in step (3) in a bone regeneration promoting drug solution, taking out and freeze-drying to obtain a bone regeneration promoting drug-loaded skull implant with a bionic structure; To better implement the present invention, further, the bone regeneration promoting drug is one of naringin and icariin, the drug concentration is 0.2 to 1 mg / mL, the drug loading time is 4 to 16 h, and the freeze-drying time is 24 to 48 h.

[0012] Beneficial effects of the present invention: (1) The bone regeneration promoting drug-loaded skull implant with a bionic structure provided by the present invention uses a water-soluble core to obtain upper and lower Haversian tube structures and a middle layer of trabecular bone-imitating structure. The upper and lower Haversian tube structures are realized by a cylindrical water-soluble core through a positioning mold design, and the middle layer of trabecular bone-imitating structure is realized by a spherical water-soluble core. The two structures are interconnected through a dissolution process, and can provide a vascularized channel and promote bone tissue climbing; (2) The bone regeneration promoting drug-loaded skull implant with a bionic structure provided by the present invention has a porous structure surface covered with a polydopamine-carboxymethyl chitosan coating, which can provide a hydration environment and promote cell climbing; (3) The drug-loaded skull implant for promoting bone regeneration with a biomimetic structure provided by the present invention has hydroxyapatite generated in situ on the surface of the polydopamine-carboxymethyl chitosan coating, and its active group phenolic hydroxyl group can chelate calcium ions and self-assemble to generate hydroxyapatite, thereby increasing the biocompatibility of the implant. The degradation of hydroxyapatite can participate in the reorganization and absorption of bone tissue and induce osteoblast osteogenesis, and its degradation does not affect the mechanical properties of the implant; (4) The bone regeneration promoting drug-loaded skull implant with a bionic structure provided by the present invention, after carboxymethyl chitosan is grafted onto polydopamine, can increase drug loading anchor points, adsorb positively charged drug molecules, and enable the drug to be continuously, stably, and efficiently released slowly, thereby promoting bone tissue regeneration. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 Schematic diagram of the drug-loaded skull implant with a bionic structure that promotes bone regeneration.

[0014] Figure 2 Schematic diagram of the transverse section of the upper and lower layers of the Haversian canal structure of the skull implant.

[0015] Figure 3 Schematic diagram of the longitudinal section of the pore structure of the middle layer of the skull implant.

[0016] Figure 4 Schematic diagram of the longitudinal section of the skull implant.

[0017] Figure 5 Results of skull implant bending strength tests.

[0018] Figure 6 Results of drug release measurements from skull implants.

[0019] Figure numerals: 1. Haversian tube-like structure; 2. intermediate layer pore structure; 3. intermediate layer; 4. hydroxyapatite; 5. drug molecule; 6. polydopamine-carboxymethyl chitosan coating. DETAILED DESCRIPTION

[0020] The present invention will be further described in detail below with reference to specific embodiments, which are intended to explain the present invention rather than to limit it.

[0021] A bone regeneration promoting drug-loaded skull implant with a bionic structure and a preparation method thereof, the specific steps are as follows:

[0022] Example 1 (1) Grind NaCl and pour it into a graphite crucible, then put it into a resistance furnace and set the temperature to 830 °C. After the furnace temperature reaches the set temperature, keep it warm for 0.5 h. Pour the molten salt into a metal mold and take out the salt core after the mold cools to room temperature. Sixteen cylindrical water-soluble cores with a diameter of 0.3 mm and a length of 4 mm were mixed with 5.06 g of PEEK and then molded to prepare the upper and lower plates of the implant containing the Haversian tube structure 1. Spherical water-soluble cores with a spherical diameter of 300 ~ 425 μm and 500 ~ 710 μm were mixed with PEEK material at a mixing ratio of 13:4 and then molded to prepare the implant middle layer plate 3 containing the middle layer pore structure 2. The cold pressing parameters were pressurizing layer by layer at 3 ~ 8 MPa, heating at 383 ℃ for 3.5 h, and pressurizing layer by layer at 3 ~ 14 MPa under hot pressing conditions for 5 min after forming. The water-soluble core was removed by water bath dissolution process to preliminarily obtain a skull implant with a bionic structure. (2) 0.1 g of polydopamine (0.2%) was dissolved in 50 mL of Tris (10 mol / L, pH 8.5), and 0.2 g of carboxymethyl chitosan (0.4%) was added and stirred for 30 h to obtain a polydopamine-carboxymethyl chitosan mixed solution. The skull implant prepared in step (1) was immersed in the mixed solution for 15 min, and dried at 60 °C for 10 min to obtain a skull implant containing a polydopamine-carboxymethyl chitosan coating 6; (3) Add 50 mL of SBF solution to a clean beaker, place the skull implant prepared in step (2) into the beaker and seal it, place it in a constant temperature water bath at 37°C, change the solution every two days, take it out after 9 days, wash it moderately with distilled water, dry it at 60°C for 10 min, and prepare hydroxyapatite 4 by biomimetic method; (4) Drug molecule 5 is naringin. 30 mg of naringin (0.5 mg / mL) is dispersed in 60 mL of PBS (pH 7.4) buffer and stirred evenly. The skull implant prepared in step (3) is immersed in the buffer for 12 h. The skull plate is placed in a freeze dryer and freeze-dried for 36 h to obtain a bone regeneration-promoting drug-loaded skull implant with a bionic structure.

[0023] Example 2 A bone regeneration promoting drug-loaded skull implant with a bionic structure, which is basically the same as Example 1, except that: In step (1), the temperature of the resistance furnace is 600°C when the water-soluble core is prepared by melt casting; 20 cylindrical water-soluble cores with a diameter of 1.4 mm and a length of 5 mm are mixed with 5.06 g of PEEK and then molded to prepare the upper and lower flat plates of the implant containing the Haversian tube structure 1; the spherical water-soluble core is mixed with PEEK at a mixing ratio of 50:1 and then molded to prepare the implant middle layer flat plate 3 containing the middle layer pore structure 2; In step (2), a mixture of 1% m / v polydopamine and 2% m / v carboxymethyl chitosan was prepared and stirred for 48 h; In step (3), the skull implant prepared in step (2) is placed in a SBF solution for 12 days; In step (4), a 1 mg / mL naringin solution is prepared, and the skull implant prepared in step (3) is immersed in the solution for 16 h.

[0024] Example 3 A bone regeneration promoting drug-loaded skull implant with a bionic structure, which is basically the same as Example 1, except that: In step (1), the temperature of the resistance furnace is 900°C when the water-soluble core is prepared by melt casting; 10 cylindrical water-soluble cores with a diameter of 0.2 mm and a length of 3 mm are mixed with 5.06 g of PEEK and then molded to prepare the upper and lower flat plates of the implant containing the Haversian tube structure 1; the spherical water-soluble core is mixed with PEEK at a mixing ratio of 1:50 and then molded to prepare the implant middle layer flat plate 3 containing the middle layer pore structure 2; In step (2), a mixture of 0.1% m / v polydopamine and 0.2% m / v carboxymethyl chitosan was prepared and stirred for 30 h; In step (3), the skull implant prepared in step (2) is placed in a SBF solution for 3 days; In step (4), a 0.2 mg / mL naringin solution is prepared, and the skull implant prepared in step (3) is immersed in the solution for 4 hours.

[0025] Example 4 A drug-loaded skull implant for promoting bone regeneration with a bionic structure, which is basically the same as Example 2, except that: In step (1), the temperature of the resistance furnace is 830°C when the water-soluble core is prepared by the melt casting method; 16 cylindrical water-soluble cores with a diameter of 1.4 mm and a length of 5 mm are mixed evenly with 5.06 g of PEEK and then molded to prepare the upper and lower flat plates of the implant containing the Haversian tube structure 1; the spherical water-soluble core is mixed evenly with PEEK in a mixing ratio of 13:4 and then molded to prepare the implant middle layer plate 3 containing the middle layer pore structure 2.

[0026] Comparative Example 1 A bone regeneration promoting drug-loaded skull implant with a bionic structure, which is basically the same as Example 1, except that: In step (3), the skull implant prepared in step (2) is placed in a solution containing SBF for 3 days.

[0027] Comparative Example 2 A bone regeneration promoting drug-loaded skull implant with a bionic structure, which is basically the same as Example 1, except that: In step (3), the skull implant prepared in step (2) is placed in a solution containing SBF for 12 days.

[0028] Comparative Example 3 A bone regeneration promoting drug-loaded skull implant with a bionic structure, which is basically the same as Example 1, except that: After step (1), there is no need to carry out step (2) of coating the polydopamine-carboxymethyl chitosan coating, and the subsequent steps (3) and (4) can be carried out directly.

[0029] Comparative Example 4 A bone regeneration promoting drug-loaded skull implant with a bionic structure, which is basically the same as Example 1, except that: In step (4), a 1 mg / mL naringin solution is prepared, and the skull implant prepared in step (3) is immersed in the solution for 16 h.

[0030] Comparative Example 5 A bone regeneration promoting drug-loaded skull implant with a bionic structure, which is basically the same as Example 1, except that: In step (4), a 0.5 mg / mL naringin solution is prepared, and the skull implant prepared in step (3) is immersed in the solution for 8 h.

[0031] Comparative Example 6 A bone regeneration promoting drug-loaded skull implant with a bionic structure, which is basically the same as Example 1, except that: In step (1), NaCl is ground and poured into a graphite crucible, which is then placed in a resistance furnace, set at 830 °C, and kept warm for 0.5 h after the furnace temperature reaches the set temperature. The molten salt is poured into a metal mold, and the salt core is taken out after the mold cools to room temperature. 5.06 g PEEK is used to mold the upper and lower flat plates of the implant, and there is no Haversian tube structure 1 in the upper and lower flat plates. Spherical water-soluble cores with spherical diameters of 300 to 425 μm and 500 to 710 μm are mixed with PEEK material at a mixing ratio of 13:4 and then molded to prepare an implant intermediate layer flat plate 3 containing an intermediate layer pore structure 2, wherein the cold pressing parameters are pressurizing layer by layer at 3 to 8 MPa, heating at 383 °C for 3.5 h, and pressurizing layer by layer at 3 to 14 MPa under hot pressing conditions, and then holding the pressure for 5 min after shaping. The water-soluble core is removed by a water bath dissolution process to preliminarily obtain a skull implant with a bionic structure.

[0032] The skull implants prepared in the above embodiments and comparative examples were subjected to cytotoxicity, bending strength, water contact angle test, porosity, calcium-phosphorus atomic ratio in the coating, drug release and other related performance tests. The specific test methods are as follows: cytotoxicity detection was performed using the MTT method; the bending strength of the implant was tested using a tensile tester; the water contact angle was tested using a contact angle tester; the porosity of the implant was measured using the Micro-CT method; the calcium-phosphorus atomic ratio in the coating was determined using inductively coupled plasma atomic emission spectrometry; and the drug release capacity of the implant at different time points in simulated body fluid was determined using a dialysis method.

[0033] The cytotoxicity results are shown in Table 1. The cytotoxicity reactions of the skull implants in the above embodiments and comparative examples are all no greater than level 2, and have no potential cytotoxicity.

[0034] Table 1 product Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Cell survival rate / % 94 90 87 89 93 90 91 95 88 92

[0035] The bending strength results are as follows Figure 5 As shown, the amount of porogen added has an effect on the mechanical properties of the implant: as the amount of water-soluble core added increases, the bending resistance of the implant decreases (Examples 1, 2, 3, 4, and Comparative Example 6).

[0036] The water contact angle test results are shown in Table 2. The sample of the embodiment has good hydrophilicity. The concentration of reactants and reaction time affect the polymer grafting and the hydrophilicity of the coating.

[0037] Table 2 product Example 1 Example 2 Example 3 Example 4 Water contact angle / ° 45 42 47 44

[0038] The porosity test results are shown in Table 3. Examples 1, 2 and the comparative example samples have higher porosity.

[0039] Table 3 product Example 1 Example 2 Example 3 Example 4 Comparative Example 6 Porosity / % 76 84 25 88 64

[0040] The results of the determination of the atomic ratio of calcium to phosphorus in the coating are shown in Table 4. Hydroxyapatite is formed in all the samples of the examples. As the reaction time increases, calcium oxide is also generated in addition to hydroxyapatite (Examples 2 and 4).

[0041] Table 4 product Example 1 Example 2 Example 3 Example 4 Calcium-phosphorus atomic ratio 1.668 1.712 1.665 1.703

[0042] Drug release test results Figure 6 As shown, the drug release rate is fast in the early stage, and then enters the sustained release stage. As the coating degrades, it is gradually released into the environment, effectively maintaining the drug concentration in the bone defect site, which is conducive to the continuous efficacy of the drug.

[0043] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A drug-loaded skull implant with a bionic structure for promoting bone regeneration, characterized in that: The skull implant has a three-layer structure, the upper and lower layers are Haversian tube-like structures, the middle layer is a trabecular bone-like structure, the porous structure of the implant is coated with a polydopamine-carboxymethyl chitosan coating, and the coating surface generates hydroxyapatite in situ and loads bone regeneration-promoting drugs; (1) The Haversian tube-like structure and the bone trabecular structure are prepared from the water-soluble core by dissolution process; The water-soluble core imitating the Haversian tube structure is cylindrical, with an average diameter of 0.2 to 1.4 mm and a length of 3 to 5 mm, and the water-soluble core imitating the trabecular structure is spherical, with a spherical diameter of 300 to 450 μm and 500 to 800 μm; (2) The porous structure of the implant is coated with a polydopamine-carboxymethyl chitosan coating; The amino groups of carboxymethyl chitosan were grafted onto the surface of polydopamine by Michael addition reaction, and the grafting time was ≥ 30 h; (3) Hydroxyapatite is generated in situ on the coating surface through a biomimetic method, and bone regeneration-promoting drug loading is achieved through electrostatic adsorption; The active group phenolic hydroxyl group on the surface of the polydopamine-carboxymethyl chitosan coating can chelate calcium ions and induce calcium and phosphorus ions provided by the SBF solution to form hydroxyapatite crystal nuclei according to the self-assembly mechanism, thereby spontaneously forming orderly and uniform hydroxyapatite on the surface of the polydopamine-carboxymethyl chitosan coating in situ; the carboxyl-modified polydopamine can electrostatically adsorb positively charged drug molecules.

2. A method for preparing the drug-loaded skull implant for promoting bone regeneration with a bionic structure according to claim 1, characterized in that: The following steps are involved: (1) A cylindrical and spherical water-soluble core was prepared as a porogen by melt casting, and then mixed with polyetheretherketone (PEEK) and molded, and a skull implant with a bionic structure was initially obtained by a dissolution process; The upper and lower layers of the skull implant are a mixture of a cylindrical water-soluble core and PEEK, and the middle layer is a mixture of a spherical water-soluble core and PEEK; (2) adding carboxymethyl chitosan to a Tris buffer solution containing polydopamine, mixing and stirring to obtain a polydopamine-carboxymethyl chitosan mixed solution, immersing the skull implant prepared in step (1) therein, taking out and drying, to obtain a skull implant containing a polydopamine-carboxymethyl chitosan coating; (3) preparing a hydroxyapatite coating by a bionic method, immersing the skull implant prepared in step (2) in a 1.5 times SBF solution in a constant temperature water bath to generate hydroxyapatite in situ, taking out and drying to obtain a skull implant containing polydopamine-carboxymethyl chitosan and a hydroxyapatite coating; (4) Immersing the implant prepared in step (3) in a bone regeneration promoting drug solution, taking out and freeze-drying to obtain a bone regeneration promoting drug-loaded skull implant with a bionic structure.

3. The method for preparing the drug-loaded skull implant for promoting bone regeneration with a bionic structure according to claim 2, characterized in that: The cylindrical water-soluble core of step (1) has an average diameter of 0.2 to 1.4 mm, a length of 3 to 5 mm, and a number of 10 to 20. The cylindrical water-soluble cores in the upper and lower layers of the implant are interconnected by a positioning mold design to form a Haversian tube structure; the spherical water-soluble core is used to simulate the trabecular bone structure of the middle layer and two spherical diameter sizes are designed, which are 300 to 450 μm and 500 to 800 μm, respectively, and the porosity is 60% to 80%, and the porosity can be adjusted by the content of the spherical water-soluble core; When the water-soluble core is prepared by the melt casting method, the temperature of the resistance furnace is 600 ~ 900 ℃, and the insulation time is 5 ~ 60 min after the furnace temperature reaches the set temperature.

4. The method for preparing the drug-loaded skull implant for promoting bone regeneration with a bionic structure according to claim 2, characterized in that: The mass ratio of the spherical water-soluble core to the PEEK mixture in step (1) is 1:50 to 50:

1.

5. The method for preparing the drug-loaded skull implant for promoting bone regeneration with a bionic structure according to claim 2, characterized in that: The molding parameters of step (1) are: cold pressing 1 ~ 20 MPa, hot pressing 1 ~ 15 MPa, holding pressure 2 ~ 10 min; hot melt temperature 300 ~ 400 ° C, heating time 1.5 ~ 5.5 h; using an ultrasonic water bath to completely precipitate the porogen.

6. The method for preparing the drug-loaded skull implant for promoting bone regeneration with a bionic structure according to claim 2, characterized in that: The concentration of the polydopamine solution in step (2) is 0.2 to 1% m / v; polydopamine and carboxymethyl chitosan undergo Michael addition reaction in an alkaline environment to be grafted onto the surface of polydopamine, the concentration of carboxymethyl chitosan is 0.2 to 2% m / v, and the grafting time is ≥30 h; the skull implant is immersed in the polydopamine-carboxymethyl chitosan coating for 1 to 20 min, the drying temperature is 60°C, and the drying time is 5 to 10 min.

7. The method for preparing the drug-loaded skull implant for promoting bone regeneration with a bionic structure according to claim 2, characterized in that: In step (3), the active groups of phenolic hydroxyl groups on the surface of the polydopamine-carboxymethyl chitosan coating can chelate calcium ions and induce calcium and phosphorus ions provided by SBF to form hydroxyapatite nuclei according to the self-assembly mechanism, thereby spontaneously forming orderly and uniform hydroxyapatite on the surface of the polydopamine-carboxymethyl chitosan coating in situ.

8. The method for preparing the drug-loaded skull implant for promoting bone regeneration with a bionic structure according to claim 2, characterized in that: In step (3), the water bath temperature is 37°C, and the soaking time is 3 to 12 days; the drying temperature is 60°C, and the drying time is 5 to 10 min.

9. The method for preparing the drug-loaded skull implant for promoting bone regeneration with a bionic structure according to claim 2, characterized in that: The bone regeneration promoting drug in step (4) is one of naringin and icariin, the drug concentration is 0.2 to 1 mg / mL, the drug loading time is 4 to 16 h, and the freeze-drying time is 24 to 48 h.

Citation Information

Patent Citations

  • Method for bonding carboxymethyl chitosan bioactive molecules on surface of magnesium alloy

    CN103657996A

  • Chitosan-based bionic bone tissue engineering scaffold and production method thereof

    CN106512099A

  • Half side slide block injection mould

    CN108748902A

  • Bone-imitating haversian system biological activity stent and preparation method and application thereof

    CN109730811A

  • Method for preparing hydroxyapatite / L-polylactide composite bone scaffold

    CN111184916A

Cited By

  • Injectable skeleton repair material and preparation method thereof

    CN121338102A

  • Method and system for preparing mechanical biological bidirectional bionic bone biological structure in special bone trabecula area at tendon / ligament bone joint

    CN121401512A

  • Method and system for preparing bone biological structure of two-way bionic of force biology special trabecular zone of tendon / ligament bone junction

    CN121401512B